Perceived Health Benefits of Exercise on Lifestyle of Civil Servants in Ilorin East Local Government, Kwara State - Surajudeen Tosho Bakinde (Indonesian Journal of Sport Management, 2022)
Abstract This study examined the health benefits of exercise on lifestyle of Civil servants of Ilorin East Local Government Area. The objective of this study were to find out if cardiovascular health, muscular endurance, body composition and flexibility as a result of exercise will influence positive lifestyle among Civil servants in the Area. Descriptive research design of survey method was adopted. The population for this study comprised all Civil servants in the area . Systematic sampling technique was used to select 10% of the population. A researcher designed structured questionnaire was used to elicit information from the respondent. A reliability coefficient of 0.65 was obtained through Pearson Product Moment Correlation (PPMC). Four null hypotheses were tested using inferential statistics of Chi-square at 0.05 alpha level. The result revealed that Cardiovascular health, Muscular endurance, Body composition, Flexibility as a result of exercise significantly influenced lifestyle among civil servants in Ilorin East Local Government positively. It was concluded that health benefits of exercise on lifestyle among Civil servants in Ilorin East. Local Government were significantly influenced by cardiovascular health, muscular endurance, body composition and flexibility as a result of exercise. Therefore, it was recommended that Civil servants should be encouraged to participate in exercise to improve their cardiovascular health.